KID WITH SPEECH DELAY AND LANGUAGE COMPETENCE EMPIRIC SOLUTION - Kudiņa, Ieva; Ratniece, Dace (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The paper explains the experience and the principles, how to teach knowingly the language and constructively communication for preschool kid with delayed speech. The external environment should be mainly calm, when necessary rigidity on setting borders should be demonstrated. Playing on the feelings, when necessary and when borders not recognized by kid. The teacher and the parent should update the attitude to kid based on experience. The teacher or the parent should grow as personality during the job with kid. The external environment should be well defined and consistent. The rules and the actions and the language with the actions should be in the everyday routine. The goal of the paper is to demonstrate the language structure, the condition for kid and examples used to communicate with kid with speech delay.